Analisis Konten Pengetahuan Terkait Virus dalam Buku Teks Biologi Sekolah Menengah untuk Penguatan Literasi Covid-19 - Lisdiana Lisdiana; Ummi Nur Afinni Dwi Jayanti (Jurnal Paedagogy, 2022)
This study aims to compare the presentation of the main content related to viruses in Biology textbooks from high schools in the Panai Hulu sub-district, Labuhan Batu district. The sample in this study is the Biology textbook used in high school class X based on the 2013 curriculum used by Senior High School/Islamic Senior High School. The research method used in this research is called “content analysis.” It is a research method taken strictly from the text through special coding and thematic classification. The data analysis technique used in this research is Thematic Content Analysis with inductive reasoning. It involves withdrawing information from an object intended to be transported optimally during observation. The results showed that the book analysis was carried out in terms of description, structure, replication, and virus prevention presented in the textbook. In terms of description, structure, replication, and prevention are still lacking in strengthening Covid-19 literacy. However, in some materials, only a few sub-sections can be used to strengthen Covid-19 literacy.